Development Strategy of Lau Debuk-Debuk Nature Park Based on Local Wisdom and Community Participation Using the Analytical Hierarchy Process (AHP) Method - Siregar, Rezki Indah; Rahmawaty, Rahmawaty; Athorick, Alief (Tunas Geografi, 2023)
The designation of the Lau Debuk Debuk forest area as a nature reserve was based on the Decree of Radja Deli dated September 30, 1934. The area underwent a change in function from a nature reserve to a tourist park, according to the Minister of Agriculture's Decree Number: 320/Kpts/Um/5/1980 dated May 9, 1980, regarding the Change of the Status of the Nature Reserve covering approximately ±7 hectares located in the Simalungun-Tanah Karo TK II Region, North Sumatra TK I Region as a Forest Tourism. In this area, there are hot springs containing sulfur. Lau Debuk-debuk Nature Park (TWA), located in the Berastagi District of Karo Regency, is one of the conservation areas managed by the North Sumatra Natural Resources Conservation Center.The research aimed to analyze local wisdom in the management of Lau Debuk-debuk Nature Park ecotourism. The study was conducted from February to May 2023 in the Lau Debuk-debuk Nature Park located in the Berastagi District of Karo Regency. It employed a qualitative approach involving local residents in the development process of strategies and the assessment of Lau Debuk-debuk Nature Park's ecotourism development based on local wisdom. The results indicate that the priority for the development of the Lau Debuk Debuk Conservation Area is the aspect of local wisdom, which is crucial for the development of a religious tourist area because it is the main reason tourists visit the natural tourist area, Lau Debuk-debuk Nature Park.Keyword: Local wisdom, ecotourism, AHP method